Synergy of STEM and Geography: Developing Critical Thinking Skills in High School Students for the Future - M Rizqon Al Musafiri; Alif Putra Lestari (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2025)
The digital age and global challenges require young people to have strong critical thinking skills. Geography, as a discipline that studies the relationship between humans and their environment, plays an important role in shaping spatial, analytical, and problem-solving skills. However, the effectiveness of geography learning in developing critical skills can be significantly improved through integration with the Science, Technology, Engineering, and Mathematics (STEM) approach. This review article aims to comprehensively analyze the synergy between STEM and Geography in building critical skills in high school students. The literature search methodology was conducted through leading scientific databases with strict inclusion criteria to identify relevant studies published in the last five years. The main findings show that the integration of STEM in geography learning not only enriches the understanding of geographical concepts but also effectively trains students in spatial data analysis, modeling, information evaluation, and solving complex problems faced in the real world. This article outlines various innovative learning strategies and implementation challenges, as well as identifying existing research gaps. The results of this review are expected to provide practical guidance for high school geography students and teachers in designing curricula and teaching methods that combine the strengths of STEM to equip students with essential critical skills in facing a dynamic future.